Analisa Hukum terhadap Benturan Kepentingan dan Penawaran Tender di Pasar Modal - Marlisa Elfira (Maliyah : Jurnal Hukum Bisnis Islam, 2020)
The opportunity to make a profit is the most important factor for investors who participate in capital market transactions. With the legal status of “PT”, this factor causes a violation of the principles of transparency and fairness in capital market transactions that have been potential to harm the rights of independent shareholders. In this study, the researcher will focus on the issue of how to identify the legal conflict of interest in the rights issue transaction conducted by PT CPRO and the implementation of the tender offer conducted by PT Philip Morris Indonesia for the remaining shares of PT HM Sampoerna Tbk. The type of research method that the researcher uses is a normative juridical study and by using a case approach. The results of this study are(1) Rights transactions carried out by CPRO, CPRO did not fully comply with existing regulations. (2) it can be seen that the acquisition that has occurred in PT. HM Sampoerna, Tbk did not cause much change, both in terms of marketing and for its employees. (3) the acquisition has made the rights of its employees more secure.